The Correlation of Digital Literacy and Acceptance of Information and Communication Technology in Bantarjaya Village Community - Saleh, Amiruddin; Santoso, Hudi; Zahra, Fatimah Az (Jurnal Penyuluhan, 2026)
There is a need for basic technological skills in the form of digital literacy as a basis for facing the digital era, to be able to accept existing information and communication technology (ICT). Moreover, the government, through Presidential Instruction Number 3 of 2003, stated that the creation of e-government focuses on transparent, efficient, and accurate communication between government, businesses, the public, and other stakeholders, including through new media (digitalization). Technological innovations are currently being promoted in villages across Indonesia to support digitalization. Digital literacy challenges remain in rural communities, leading to low acceptance of ICT in terms of perceived usefulness and perceived ease of use. ICT acceptance can be measured using the Technology Acceptance Model (TAM). This study aims to analyze the level of digital literacy and ICT acceptance in society, as well as to analyze the relationship between digital literacy and individual characteristics and ICT acceptance. The research used a quantitative approach with a survey method for 54 respondents, and qualitative data. The results of the study indicate that 1) digital literacy in Bantarjaya Village is in the moderate category; 2) ICT acceptance in Bantarjaya Village shows moderate results; 3) There is a significant relationship between individual characteristics including age, education, occupation, and number of gadgets owned with digital literacy; 4) and there is a significant relationship between digital literacy and acceptance of information and communication technology in the technology acceptance model.